Normative pattern and determinants of outer retinal thickness in an Asian population: the Singapore Epidemiology of Eye Diseases Study. Issue 10 (18th January 2019) - Dai, Wei; Tham, Yih-Chung; Chee, Miao-Li; Majithia, Shivani; Tan, Nicholas Y Q; Wong, Kah-Hie; Neelam, Kumari; Cheung, Ning; Sabanayagam, Charumathi; Cheung, Carol Y; Wong, Tien-Yin; Cheng, Ching-Yu
Abstract : Background/aims: To evaluate the distribution and determinants of outer retinal thickness in eyes without retinal diseases, using spectral-domain optical coherence tomography (SD-OCT). Methods: Participants were recruited from the Singapore Epidemiology of Eye Diseases Study, a population-based study among Chinese, Malays and Indians in Singapore. A total of 5333 participants underwent SD-OCT imaging in which a 6×6 mm 2 measurement area centred at the fovea. Outer retinal thickness was defined as the distance from the outer plexiform layer to the retinal pigment epithelium layer boundary. Results: 7444 eyes from 4454 participants were included in final analysis. Of them, mean age was 58.4 years (SD 8.3), and 2294 (51.5%) were women. Women (121.0±8.1 µm) had thinner average outer retinal thickness than men (125.6±8.2 µm) (p<0.001). Malays (121.4±8.7 µm) had thinner average outer retinal thickness than Indians (124.3±8.6 µm) and Chinese (123.7±7.9 µm) (both p<0.001). In multivariable models, thinner average outer retinal thickness was associated with older age (per decade, β=−1.02, p<0.001), hypertension (β=−0.59, p=0.029), diabetes (β=−0.73, p=0.013), chronic kidney disease (β=−1.25, p=0.017), longer axial length (per mm, β=−0.76, p<0.001), flatter corneal curvature (per mm, β=−2.00, p<0.001) and higher signal strength (β=−1.46, p<0.001). Conclusion: In this large sample of Asian population, we provided normative SD-OCT data on outer retinal thickness in eyes without retinal diseases. Women had thinner outer retina than men. For the first time, these findings provide fundamental knowledge on normative profile of outer retinal thickness in Asians.